2021
DOI: 10.21203/rs.3.rs-705506/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation and Characterization of Copper Tolerant Bacterial Species Habituating in Copper Mines and Study of Their Potentiality as a Plant Growth Stimulator

Abstract: Copper (Cu) is a vital micronutrient for all living organisms below its toxicity limit. Various industrial activities, mining deposits, excessive use of harmful chemicals, waste discharges, and drugs are the main reason for the emerging copper concentration. Emphases of the current study were to isolate and characterize highly copper-tolerating bacterial (CTB) species from a copper-contaminated site. In enrichment culture techniques, 24 copper tolerant microbial isolates were evaluated and the maximum tolerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
2
0
0
Order By: Relevance
“…Out of 20 heavy metal‐resistant bacterial isolates, only 04 isolates were further studied based on their ability to resist high concentrations of FeSO 4 .7H 2 O and CuSO 4 .5H 2 O. The growth capacities of iron and copper tolerant isolates at different temperatures (4°C, 25°C, 37°C, and 45°C) and varying pH (2.0, 4.0, 7.0, 8.0, and 10.0) values were demonstrated in our result, showing that the maximum growth of isolates was found at 37°C and pH 7 after incubation of 24 h. This is consistent with the result of earlier studies where the growth was observed at 37°C and pH 7 [56]. Among all heavy metal‐tolerant bacterial strains, Pantoea sp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Out of 20 heavy metal‐resistant bacterial isolates, only 04 isolates were further studied based on their ability to resist high concentrations of FeSO 4 .7H 2 O and CuSO 4 .5H 2 O. The growth capacities of iron and copper tolerant isolates at different temperatures (4°C, 25°C, 37°C, and 45°C) and varying pH (2.0, 4.0, 7.0, 8.0, and 10.0) values were demonstrated in our result, showing that the maximum growth of isolates was found at 37°C and pH 7 after incubation of 24 h. This is consistent with the result of earlier studies where the growth was observed at 37°C and pH 7 [56]. Among all heavy metal‐tolerant bacterial strains, Pantoea sp.…”
Section: Discussionsupporting
confidence: 93%
“…The bacterial strains SC5, SC8, and SC10 showed high tolerance to Fe (FeSO 4 .7H 2 O) upto 700 μg/mL, followed by bacterial strains GN2 with heavy metal tolerance upto the other hand, some findings demonstrated that P. agglomerans were tolerant to Cu, having a MIC value of 7 mM [55]. Out of 20 heavy metal-resistant bacterial isolates, only 04 isolates were further studied based on their ability to resist high concentrations of FeSO showing that the maximum growth of isolates was found at 37°C and pH 7 after incubation of 24 h. This is consistent with the result of earlier studies where the growth was observed at 37°C and pH 7 [56]. Among all heavy metal-tolerant bacterial strains, Pantoea sp.…”
Section: Discussionsupporting
confidence: 88%